Characterization of Carbapenemase- and ESBL-Producing Gram-Negative Bacilli Isolated from Patients with Urinary Tract and Bloodstream Infections - Isabella A. Tickler; Diane Kawa; Anne E. Obradovich; Ferric C. Fang; Fred C. Tenover; the Healthcare Associated Infections Consortium (MDPI AG, 2023)
A total of 199 Gram-negative bacterial isolates from urinary tract infections and 162 from bloodstream infections were collected from 12 healthcare systems throughout the United States between May 2021 and August 2022. The isolates, phenotypically non-susceptible to 2nd or 3rd generation cephalosporins or carbapenems, were characterized through antimicrobial susceptibility testing and whole genome sequence analysis to obtain a broad snapshot of beta-lactamase-mediated resistance among these two sample types. Overall, 23 different carbapenemase genes were detected among 13 species (20.5% of isolates). The blaKPC-3 and blaKPC-2 subtypes were the most common carbapenemase genes identified, followed by blaNDM and the co-carriage of two different blaOXA carbapenemases by Acinetobacter baumannii isolates. All carbapenemase-producing A. baumannii isolates were mCIM negative. Extended-spectrum beta-lactamase genes were identified in 66.2% of isolates; blaCTX-M-15 was the most common. AmpC genes, both plasmid and chromosomal, were detected in 33.2% of isolates. Importantly, 2.8%, 8.3%, and 22.2% of blaKPC-positive organisms were susceptible to ertapenem, imipenem, and meropenem, respectively. The correlation between broth microdilution and disk diffusion results was high for most drugs except cefepime, where the detection of resistance was statistically lower by disk diffusion. Thus, there were gaps in the accuracy of susceptibility testing for some mechanisms of resistance.